Organizational Effectiveness of the Regional Revenue Agency in Hotel Tax Collection in Dumai City - Lilis Wahyuni; Indah Kumala Dewi; Erinaldi Erinaldi (International Journal of Humanities and Social Sciences Reviews, 2024)
This study aims to analyze the effectiveness of the Regional Revenue Agency (Bapenda) in collecting hotel taxes in Dumai City. Using a qualitative approach with a case study method, this study explores the factors influencing the effectiveness of tax collection and the obstacles encountered. Data were collected through in-depth interviews, observations, and documentation, which were then analyzed using thematic analysis. The results indicate that although the objectives of tax collection have been clearly defined and provide benefits for regional development, several obstacles still hinder the achievement of the expected targets. The main obstacles include a lack of coordination between relevant parties, immature planning, and policies that are not yet fully effective. In addition, bad debts on hotel taxes are a major challenge that affects the effectiveness of tax collection. This study also found that a broad socialization strategy and the provision of adequate infrastructure have helped increase taxpayer awareness and compliance. However, supervision and control need to be improved to prevent irregularities and ensure taxpayer compliance. By improving coordination, more detailed planning, data-driven policies, more intensive education, the use of information technology, and stricter supervision, it is hoped that the effectiveness of hotel tax collection can be significantly improved. This research provides an important contribution to the Dumai City Bapenda and other local governments in their efforts to improve the effectiveness of regional tax collection. It is hoped that the recommendations provided can be implemented to overcome existing obstacles and increase regional original income (PAD) in a sustainable manner.